2020
DOI: 10.3390/su12031200
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Real and Virtual Construction Field Trips on Students’ Perception and Career Aspiration

Abstract: To adequately prepare students for engineering practices, it is imperative that institutions adopt innovative methods of teaching, learning, and assessment. One such approach is the use of real field trips (RFT) to construction sites, which can enhance students’ perceptions of related careers. Although virtual field trips (VFTs) have emerged as a viable alternative—or supplement—to traditional field trips, little is known about their potential to provide the same or similar career exploration advantages. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 29 publications
4
39
0
Order By: Relevance
“…It can be seen that the students repeated the words “course”, “teaching”, “online”, “F2F” and “teacher” more than any others. The first four words are closely related to the subject matter addressed in the survey, the analysis of which is irrelevant, as indicated in other similar studies [ 55 ]. However, the word “teacher” is not directly related to the situation under study and reinforces the abovementioned aspect: the great importance that students attributed to the teacher in both types of teaching, but with special emphasis on online teaching.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…It can be seen that the students repeated the words “course”, “teaching”, “online”, “F2F” and “teacher” more than any others. The first four words are closely related to the subject matter addressed in the survey, the analysis of which is irrelevant, as indicated in other similar studies [ 55 ]. However, the word “teacher” is not directly related to the situation under study and reinforces the abovementioned aspect: the great importance that students attributed to the teacher in both types of teaching, but with special emphasis on online teaching.…”
Section: Resultsmentioning
confidence: 98%
“…The purpose of the last questions of the survey was to establish whether the students considered that the course had been difficult to understand (statement 17) or to pass (statement 18), whether they thought they had learned (statement 19), and whether they had a high workload (statement 20). These direct questions (see Section 2.5 ) were asked to elicit replies from the students that were focused on the specific aspects that the authors of this research work wished to analyze [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies conducted on the effectiveness of field trips in enhancing the learning experience and development showed that students remember more what they had learned in the classroom when they participated in field trips (Behrendt & Franklin, 2014;Bowen, 2014;Kennedy, 2014;Krakowka, 2012;Mahgoub & Alawad, 2014;Manner, 2018;Myers & Jones, 2004). Field trips have been used as part of the teaching and learning process in many fields, including arts (Mahgoub & Alawad, 2014), geography (Ilovan, Dulama, Nagy & Adorean, 2019;Krakowka, 2012;Latipah, Ruhimat & Somantri, 2019;Preston, 2016), science (Behrendt & Franklin, 2014), engineering (Hanh & Hop, 2018;Seifan, Dada & Berenjian, 2020) and even law (Higgins, Dewhurst & Watkins, 2012;Nawi & Fuziana, 2016).…”
Section: Introductionmentioning
confidence: 99%